The use of sequential extraction procedure for mercury fractionation study in gold mining tailings: implications for environmental pollution - Budianta, Wawan; Idrus, Arifudin; Hakim, Fahmi; Resurrection, Augustus C.; Hinode, Hirofumi (Journal of Degraded and Mining Lands Management, 2026)
Artisanal and small-scale gold mining (ASGM) activities still use mercury (Hg) for the amalgamation processing step. These ASGM activities generate tailings as a mining by-product, representing the primary source of environmental Hg contamination. The purpose of this study was to investigate Hg concentrations in several tailing ponds and analyze the fractionation of Hg in tailings in ASGM on Banyumas District, Central Java, Indonesia. In total, 15 tailings samples were taken from the ASGM tailings storage pond in the study area, and then the total Hg concentration was measured using cold vapor atomic fluorescence spectrometry (CVAFS). Hg fractionation was also performed using CVAFS. The results showed that the total Hg concentration in the tailing pond was very high, exceeding the normal background levels in rock or sediment due to ASGM activities. The fractionation analysis conducted to determine Hg mobility showed that almost all samples were concentrated in the first and second fractions, which had negative environmental effects. The findings from the mercury speciation analysis highlight the critical need for enhanced monitoring of gold mining operations and for implementing responsible tailings management strategies to prevent environmental pollution and protect ecosystem health in the study area.